A Review: Production of Analog Rice from Mocaf and Soybean-Based Flours for Food Diversification - Aam Sahal Mushoffi; Heny Kusumayanti (Journal of Innovative and Creativity, 2025)
Rice is the main staple food for most populations, leading to high consumption rates and dependency on a single food source. Developing analog rice from local and sustainable ingredients is an effective approach to promote food diversification and reduce reliance on conventional rice. This review examines the production of analog rice using Modified Cassava Flour (Mocaf) and soybean flour as complementary materials. Mocaf provides carbohydrates and a suitable starch matrix, while soybean flour enhances protein, fiber, and nutrient content. The extrusion process is commonly applied due to its efficiency in blending, gelatinization, and shaping. Previous studies indicate that analog rice made from mocaf–soybean blends has higher protein content (8–12%), balanced moisture levels, and a lower glycemic index compared to white rice. These characteristics highlight the potential of mocaf–soybean analog rice as a functional and nutritious food that supports food diversification and contributes to nutritional improvement.